Androgens and androgen receptor action in skin and hair follicles - Ceruti, Julieta María (2018)
Beyond sexual functions, androgens exert their action in skin physiology andpathophysiology. Skin cells are able to synthesize most of active androgens from gonadal or adrenal precursors and the enzymes involved in skin steroidogenesis are implicated both in normal or pathological processes. Even when the role of androgens and androgen receptor (AR) in skin pathologies has been studied for decades, their molecular mechanisms in skin disorders remain largely unknown. Here, we go over recent studies of androgens and AR roles in several skin-related disorders, focusing in the current understanding of its molecular mechanisms in androgenetic alopecia (AGA). We review on the molecular pathophysiology of type 2 5α-reductase, AR coactivators, the paracrinefactors deregulated in dermal papilla (such as TGF-β, IGF 1, WNTs and DKK-1) and the crosstalk between AR and Wnt signaling in order to shed some light on new promising treatments.